Microsoft SQL server 2012 : management and administration - Mistry, Ross (Sams, 2013)
If you need to deploy, manage, or secure Microsoft SQL Server 2012, this is the complete, fast-paced, task-based reference you've been searching for. Authored by a worldclass expert on running SQL Server in the enterprise, this book goes far beyond the basics, taking on the complex tasks that DBAs need to make the most of Microsoft's first cloud-enabled database platform. Designed for maximum practical usability, it's packed with expert tips and up-to-date real-world configuration guidance you simply won't find anywhere else. As someone who helped influence the design of SQL Server 2012 and drawing on many months of beta testing, Ross Mistry provides immediately usable solutions for installation and upgrades, management and monitoring, performance and availability, security, consolidation, virtualization, troubleshooting, and more. Mistry identifies new features and corresponding best practices in every chapter, helping you take full advantage of new SQL Server innovations ranging from private cloud support to AlwaysOn Availability Groups. Understand how to: Efficiently install or upgrade the SQL Server 2012 database engine Administer and configure database engine settings, storage, I/O, and partitioning Transfer data on-premise or to the cloud Manage and optimize indexes Learn how to consolidate, virtualize and optimize SQL Server for Private Clouds Harden and audit SQL Server 2012 environments Administer security and authorization, including new Contained Databases Encrypt data and communications Design and deploy new AlwaysOn high-availability and disaster recovery features Implement maintenance best practices, including Policy-Based Management.